Poverty, Disparities and Human Development on Sustainability Development - Nuraini, Siti; Ardianti, Riski Isminar; Millati, Izzato; Tjaraka, Heru (International Journal of Psychosocial Rehabilitation, 2020)
Decreasing poverty line and improving the quality of human development is one of the objectives of development in Indonesia. Poverty has an impact multisectoral, not only concerning about household income but also the ability of households improves the quality of his life, that could be improve regional income. Poverty can cause disparities income in aech regencies or cities. The purpose of this research is look for the relations of poverty toward regional income, disparities, and human qualities. These researches used quantitative descriptive method by rekursif generalized component structured analysis (GSCA) with research areas in East Java. In GSCA, variable latent defined as a component of weight or aggregate of the indicators. This result of this research seen the model FIT of 76% and a component root mean square of 0.08% indicates that the overall model could be used and well received. Poverty has an impact to disparities as a direct and to regional income as an indirect, but poverty has not affected to human development and regional income.